2022
DOI: 10.7717/peerj.13245
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gut microbiome in the Chinese mud snail (Cipangopaludina chinensis) and the invasive golden apple snail (Pomacea canaliculata)

Abstract: Background Gut microbiota play a critical role in nutrition absorption and environmental adaptation and can affect the biological characteristics of host animals. The invasive golden apple snail (Pomacea canaliculata) and native Chinese mud snail (Cipangopaludina chinensis) are two sympatric freshwater snails with similar ecological niche in southern China. However, gut microbiota comparison of interspecies remains unclear. Comparing the difference of gut microbiota between the invasive snail P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 67 publications
5
11
1
Order By: Relevance
“…The results are consistent with the findings of recent studies in other Cipangopaludina species ( Zhou K. Q. et al, 2022 ; Zhou Z. H. et al, 2022 ). The other two dominant phyla were Bacteroidetes and Firmicutes, which are consistent with the findings of previous studies that have reported that the major bacterial phyla in the gut of aquatic animals, including fish, crustaceans, and mollusks are Proteobacteria, Bacteroidetes, and Firmicutes ( Chang et al, 2019 ; Liu et al, 2019 ; Wang et al, 2020b ; Zhang Y. et al, 2020 ; Zhou Z. H. et al, 2022 ). However, the two phyla were not dominant in a closely related species, Cipangopaludina chinensis ( Zhou K. Q. et al, 2022 ; Zhou Z. H. et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results are consistent with the findings of recent studies in other Cipangopaludina species ( Zhou K. Q. et al, 2022 ; Zhou Z. H. et al, 2022 ). The other two dominant phyla were Bacteroidetes and Firmicutes, which are consistent with the findings of previous studies that have reported that the major bacterial phyla in the gut of aquatic animals, including fish, crustaceans, and mollusks are Proteobacteria, Bacteroidetes, and Firmicutes ( Chang et al, 2019 ; Liu et al, 2019 ; Wang et al, 2020b ; Zhang Y. et al, 2020 ; Zhou Z. H. et al, 2022 ). However, the two phyla were not dominant in a closely related species, Cipangopaludina chinensis ( Zhou K. Q. et al, 2022 ; Zhou Z. H. et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
“…The other two dominant phyla were Bacteroidetes and Firmicutes, which are consistent with the findings of previous studies that have reported that the major bacterial phyla in the gut of aquatic animals, including fish, crustaceans, and mollusks are Proteobacteria, Bacteroidetes, and Firmicutes ( Chang et al, 2019 ; Liu et al, 2019 ; Wang et al, 2020b ; Zhang Y. et al, 2020 ; Zhou Z. H. et al, 2022 ). However, the two phyla were not dominant in a closely related species, Cipangopaludina chinensis ( Zhou K. Q. et al, 2022 ; Zhou Z. H. et al, 2022 ). The result implies that although the two species are closely related, they may have different strategies of responding to Cd stress.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, Proteobacteria, Bacteroidetes, and Firmicutes were the three dominant phyla across all treatment groups, which is consistent with previous findings in mollusks [ 47 , 48 ]. However, Bacteroidetes and Firmicutes were not the dominant phyla in a closely related species, Cipangopaludina chinensis [ 48 , 49 ].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, Proteobacteria, Bacteroidetes, and Firmicutes were the three dominant phyla across all treatment groups, which is consistent with previous findings in mollusks [ 47 , 48 ]. However, Bacteroidetes and Firmicutes were not the dominant phyla in a closely related species, Cipangopaludina chinensis [ 48 , 49 ]. This inconsistency implies that although the two species are closely related, they may have different strategies of responding to high-temperature stress [ 28 , 29 , 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…Significant differences were found in the structure of gut microbiota among female, male, and juvenile groups, suggesting the gut microbiota of P. canaliculata has been affected by the developmental stages (Chen et al, 2021 ). Zhou et al ( 2022 ) investigated difference of gut microbiota between P. canaliculata and native snail Cipangopaludina chinensis . The results found that there were marked differences in the gut microbiota structure between P. canaliculata and C. chinensis .…”
Section: Introductionmentioning
confidence: 99%